Biochemic Treatment – An Adjuvant to Homoeopathy (Homoeopathy for All, 2025)
Background: The biochemic system of medicine, developed by Schüssler, is often used as an adjuvant to homoeopathic treatment without interfering with the action of homoeopathic remedies.Case Presentation: A 55-year-old woman presented with severe thrombosed external piles, associated with excruciating pain, redness, swelling (the size of a one-rupee coin), and constipation. She had difficulty sitting and walking. Conventional homoeopathic medicines such as Aesculus, Collinsonia, Ratanhia, Nux vomica, and Sulphur were prescribed, but no improvement was observed over five days. Surgical consultation suggested conservative measures before considering operative intervention.Intervention: Based on Schüssler’s biochemic remedies, Calcarea fluorica 12x was prescribed in frequent doses (10 tablets every two hours, either directly or dissolved in lukewarm water)Outcome: Within 24 hours, the patient reported 70% relief in pain and swelling. After one week of continued treatment, complete resolution of swelling, pain, itching, and constipation was observed.Conclusion: This case demonstrates the efficacy of biochemic remedies, specifically Calcarea fluorica, as an effective adjunct to homoeopathic treatment in managing acute conditions such as thrombosed piles.
Keywords: biochemic; system; medicine; Schüssler; constipation